Analisa Keandalan Instrumentasi Pada Pulp Dryer Unit Menggunakan Metode Reliability Centered Maintenance (RCM) di PT. Indah Kiat Pulp and Paper Perawang - Syukma, Angga Syukma; Jufrizel, Jufrizel; Ullah, Aulia; Mursyitah, Dian (Universitas Al Azhar Indonesia, 2024)
PT. Indah Kiat Pulp and Paper Perawang, a backup of Sinarmas, is one of the biggest companies concurring to the Indonesia Stock Trade. One of the most critical units in the production process is the pulp dryer unit, with an estimated production capacity of 657 tons per day. Based on the data obtained, the pulp dryer unit frequently experiences failures that disrupt the production process. This ponder utilizes the RCM (Reliability Centered Maintenance) strategy to decide which gadgets within the mash dryer unit are most inclined to issues by calculating the RPN (Risk Priority Number) for each component, assessing the unwavering quality level of these gadgets, and giving proposals for an ideal support plan. The think about comes about appear the RPN values for mash dryer instrumented from most elevated to least as takes after: temperature sensor at 392, press transmitter at 288, level transmitter at 280, stream transmitter at 252, solenoid valve at 252, consistency transmitter at 245, and on/off valve at 210. The unwavering quality values for each instrumented component that did not meet the edge set by the SII (Indonesian Industrial Standards), which is 0.7, demonstrate the require for support activities. The recommended maintenance schedule for the instrumentation is as follows: temperature sensor at 252 days, press transmitter at 352 days, level transmitter at 352 days, flow transmitter at 352 days, solenoid valve at 352 days, consistency transmitter at 293 days, and on/off valve at 440 days.Keywords – FMEA, Instrumentation, Reliability, Pulp Dryer, RCM.